A retained intron in the 3′‐UTR of Calm3 mRNA mediates its Staufen2‐ and activity‐dependent localization to neuronal dendrites. (1st August 2017) - Sharangdhar, Tejaswini; Sugimoto, Yoichiro; Heraud‐Farlow, Jacqueline; Fernández‐Moya, Sandra M; Ehses, Janina; Ruiz de los Mozos, Igor; Ule, Jernej; Kiebler, Michael A
Abstract: Dendritic localization and hence local mRNA translation contributes to synaptic plasticity in neurons. Staufen2 (Stau2) is a well‐known neuronal double‐stranded RNA‐binding protein (dsRBP) that has been implicated in dendritic mRNA localization. The specificity of Stau2 binding to its target mRNAs remains elusive. Using individual‐nucleotide resolution CLIP (iCLIP), we identified significantly enriched Stau2 binding to the 3′‐UTRs of 356 transcripts. In 28 (7.9%) of those, binding occurred to a retained intron in their 3′‐UTR. The strongest bound 3′‐UTR intron was present in the longest isoform of Calmodulin 3 ( Calm3 L ) mRNA. Calm3 L 3′‐UTR contains six Stau2 crosslink clusters, four of which are in this retained 3′‐UTR intron. The Calm3 L mRNA localized to neuronal dendrites, while lack of the 3′‐UTR intron impaired its dendritic localization. Importantly, Stau2 mediates this dendritic localization via the 3′‐UTR intron, without affecting its stability. Also, NMDA‐mediated synaptic activity specifically promoted the dendritic mRNA localization of the Calm3 L isoform, while inhibition of synaptic activity reduced it substantially. Together, our results identify the retained intron as a critical element in recruiting Stau2, which then allows for the localization of Calm3 L mRNA to distal dendrites. Synopsis: This study shows that Stau2 binds 28 transcripts through a retained intron in their 3′‐UTR. Stau2 binding to the 3′‐UTR intron and synaptic activity both promote the dendritic localization of Calm3 mRNA. Stau2 binds to retained introns in 3′‐UTRs of several neuronal mRNAs, including Calm3 . Stau2 specifically interacts with a retained intron of the long Calm3 mRNA isoform ( Calm3 L ). Stau2 mediates dendritic localization of Calm3 L mRNA in mature hippocampal neurons. Synaptic activity induces dendritic localization of Calm3 L mRNA. Abstract : This study shows that Stau2 binds 28 transcripts through a retained intron in their 3′‐UTR. Stau2 binding to the 3′‐UTR intron and synaptic activity both promote the dendritic localization of Calm3 mRNA.